Interaction of the serotonin transporter-linked polymorphic region and environmental adversity: increased amygdala-hypothalamus connectivity as a potential mechanism linking neural and endocrine hyperreactivity - Alexander, Nina Carmen; Koppe, Georgia (Biological psychiatry, 2012)
BACKGROUND: Gene by environment (G×E) interaction between genetic variation in the promoter region of the serotonin transporter gene (serotonin transporter-linked polymorphic region [5-HTTLPR]) and stressful life events (SLEs) has been extensively studied in the context of depression. Recent findings suggest increased neural and endocrine stress sensitivity as a possible mechanism conveying elevated vulnerability to psychopathology. Furthermore, these G×E mediated alterations very likely reflect interrelated biological processes. METHODS: In the present functional magnetic resonance imaging study, amygdala reactivity to fearful stimuli was assessed in healthy male adults (n = 44), who were previously found to differ with regard to endocrine stress reactivity as a function of 5-HTTLPR × SLEs. Furthermore, functional connectivity between the amygdala and the hypothalamus was measured as a potential mechanism linking elevated neural and endocrine responses during stressful/threatening situations. The study sample was carefully preselected regarding 5-HTTLPR genotype and SLEs. RESULTS: We report significant G×E interaction on neural response patterns and functional amygdala-hypothalamus connectivity. Specifically, homozygous carriers of the 5-HTTLPR S' allele with a history of SLEs (S'S'/high SLEs group) displayed elevated bilateral amygdala activation in response to fearful faces. Within the same sample, a comparable G×E interaction effect has previously been demonstrated regarding increased cortisol reactivity, indicating a cross-validation of heightened biological stress sensitivity. Furthermore, S'S'/high SLEs subjects were characterized by an increased functional coupling between the right amygdala and the hypothalamus, thus indicating a potential link between neural and endocrine hyperreactivity. CONCLUSIONS: The present findings contribute to the ongoing debate on 5-HTTLPR × SLEs interaction and are discussed with respect to clinical implications.
Gesehen am 23.04.2018